2011
DOI: 10.1557/opl.2011.585
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of transition-metal and rare-earth doped III-nitride semiconductors for spintronics

Abstract: Transition metal (Cr) and rare-earth (Dd, Dy) doped III-nitride semiconductor bulk layers and superlattice (SL) structures are grown on sapphire (0001) substrates and GaN (0001) templates by plasma-assisted molecular-beam epitaxy. For the GaGdN/GaN and InGaGdN/GaN SL and Si co-doped samples, enhancement of magnetization and magnetic moment are observed, suggesting the carrier-mediated ferromagnetism. Low temperature growth of GaGdN can increase the Gd concentration and magnetization. Results for the Dy-doped G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It may thus indeed indicate a significant incorporation of Ga vacancies, even overcompensating the expected increase in lattice constant due to Gd. In contrast, Asahi et al 5 reported an increase in lattice constant up to a certain concentration of Gd. After that, the samples were found to contain GdN precipitates which would releave the strain.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…It may thus indeed indicate a significant incorporation of Ga vacancies, even overcompensating the expected increase in lattice constant due to Gd. In contrast, Asahi et al 5 reported an increase in lattice constant up to a certain concentration of Gd. After that, the samples were found to contain GdN precipitates which would releave the strain.…”
mentioning
confidence: 83%
“…After that, the samples were found to contain GdN precipitates which would releave the strain. In order to incoporate larger concentrations of Gd without GdN formation, the group of Asahi et al 5 used lower temperature growth. In these samples reported by Asahi et al 5 the magnetic moment per Gd is typically less than the nominal 7µ B per Gd 3+ except at the highest concentrations in contrast to the group of Dhar et al…”
mentioning
confidence: 99%